Metrics, Money, and Managerialism: Faculty Experiences of Competing Logics in Higher Education. (2nd January 2020) - Vican, Shawna; Friedman, Asia; Andreasen, Robin
ABSTRACT: Higher education faces a conflict between the traditional logic of professionalism and an increasingly prominent corporate logic. Using interviews with 30 faculty at a single institution, we seek to understand the consequences of these competing logics. Across our interviews, faculty express a misalignment between their professional values and the corporate logic applied by administrators. This incompatibility contributes to faculty dissatisfaction, much of which is centered around three themes: increasing managerial control, quantification of faculty performance using commensurable metrics, and the university's financial climate, where generating revenue is perceived to take priority over educational mission. We identify four strategies faculty employ to manage conflicting logics: respondents resist the corporate logic through collective action, insulate themselves by engaging with a community of colleagues who share their professional logic, disengage from fully participating in university life, and consider moving to an institution where the corporate logic is less prevalent. We argue that the institutional logics framework confers several analytic advantages. As a meta-theory that specifies cross-level effects between individual actors, organizations, fields, and institutional orders, it provides a framework to capture top-down and bottom-up change, providing a more robust and inclusive understanding of how corporate logic is being incorporated into higher education.